PELATIHAN BACA TULIS UNTUK USIA DINI DI DESA CIPEUNDEUY - Ul Agnia, Syifa; Andi Riana, Angga; Alfarizy, Muhammad Arya (HARUPAT: Jurnal Pengabdian Masyarakat Multidisiplin, 2025)
This literacy training aims to improve basic literacy skills of early childhood in Cipeundeuy Village. This activity is based on the low reading and writing skills of preschool children, especially those who are not reached by formal PAUD or kindergarten services. The methods used include a play-and-learn approach, the use of visual media, and direct assistance by the facilitator. The results of the activity showed a significant increase in positive impact on improving children's basic literacy skills, especially in terms of letter recognition, syllable pronunciation, and the ability to write one's own name. An interactive, fun, and developmentally appropriate approach to play while learning has been shown to be effective in increasing their motivation and active involvement in the learning process. Parental involvement in helping children learn at home also strengthens training outcomes, while creating a consistent learning environment between home and community. In addition, the involvement of KKN students in designing and facilitating programs shows a great contribution in forming an inclusive and participatory education ecosystem at the village level. It is hoped that this activity will be the first step to strengthen the foundation of early childhood literacy in rural areas